2011
DOI: 10.1007/s10886-011-9993-5
|View full text |Cite
|
Sign up to set email alerts
|

Smelling the Wood from the Trees: Non-Linear Parasitoid Responses to Volatile Attractants Produced by Wild and Cultivated Cabbage

Abstract: Despite a large number of studies on herbivore-induced plant volatiles (HIPVs), little is known about which specific compounds are used by natural enemies to locate prey- or host- infested plants. In addition, the role of HIPVs in attracting natural enemies has been restricted largely to agricultural systems. Differences in volatile blends emitted by cultivars and plants that originate from wild populations may be attributed to potentially contrasting selection regimes: natural selection among the wild types a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 49 publications
2
72
0
Order By: Relevance
“…Plants may indirectly affect the natural enemy community exploiting their herbivorous pests by mediating multitrophic interactions 57 . In this respect, the possibility of using plant volatiles to manipulate predator behaviour is promising when the purpose is to enhance the biological control of crop pests 58 or control populations of invasive predators 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Plants may indirectly affect the natural enemy community exploiting their herbivorous pests by mediating multitrophic interactions 57 . In this respect, the possibility of using plant volatiles to manipulate predator behaviour is promising when the purpose is to enhance the biological control of crop pests 58 or control populations of invasive predators 46 .…”
Section: Discussionmentioning
confidence: 99%
“…; Gols et al . ). Many laboratory studies have demonstrated that HIPVs make plants more attractive to host‐seeking natural enemies (van Poecke et al .…”
Section: Introductionmentioning
confidence: 97%
“…Insect behavior studies show that 3-pentanol plays a critical role as a pheromone in the sexual communication of M. mutates [21]. In addition, 3-pentanol is produced by wild Brassica oleracea plants in response to infestation by the caterpillars Pieris rapae and Plutella xylostella [23,24]. Plants were recently shown to produce 3-pentanol as an olfactory stimulus.…”
Section: Introductionmentioning
confidence: 99%